A meta-analytic evaluation of the efficacy and safety of levetiracetam for treating myoclonic seizures - Sara Najafi; Mohaddeseh Sadat Alavi; Hamid Reza Sadeghnia (Heliyon)
Levetiracetam (LEV) is a broad-spectrum antiseizure medication that is effective and safe in myoclonic seizures. This study aims to systematically review and meta-analyze the literature using LEV in myoclonic seizures and its efficacy and safety profile.The included literature is updated till February 2024. Joanna Briggs Institute checklists were utilized for quality assessment. Publication details, general characteristics, and the details of the LEV treatment were extracted from the included papers. Finally, the data was meta-analyzed and publication bias was assessed.52 studies were included in the meta-analysis. Considering the reduction of seizures by more than 50 % after the administration of LEV as a responder rate, 59.72 % of patients with myoclonic seizures significantly responded. Moreover, a significant percentage of the patients (37.82 %) became seizure-free after the treatment. 13.86 % of the patients discontinued the consumption of LEV due to adverse effects, lack of remission of the seizure, or unwillingness. Pre-to post-data analysis in the LEV group demonstrated a significant decline of 0.9 times in the mean number of myoclonic seizures per month.LEV significantly reduced the occurrence of myoclonic seizures. Furthermore, it is well-tolerated and responsible for a few side-effects. However, it is necessary to monitor carefully LEV's individual response.